2019
DOI: 10.1590/2179-8087.100617
|View full text |Cite
|
Sign up to set email alerts
|

Production of Structural Particleboard of Mimosa Scabrella Benth With Lignin Phenol-formaldehyde Resin

Abstract: The objective of this work was to evaluate the feasibility of using lignin-phenol-formaldehyde resin in the production of Mimosa scabrella Benth (bracatinga) structural particleboard. The boards were produced with nominal specific mass of 0.75 and 0.95 g/cm3, 10% and 12% of phenol-formaldehyde and lignin-phenol-formaldehyde resins, with 10 and 12 min of pressing time. The boards quality was evaluated by means of the following physical-mechanical tests: specific mass, compression ratio, water absorption and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
5
1
Order By: Relevance
“…The mean values of WA and TS after 2 and 24 h of immersion in water obtained in this study were also higher than the results reported by some researchers [62] in particleboards produced with lignin-phenol-formaldehyde resin with density of 750 and 950 kg/m 3 . In other works [38,40], it was also indicated that manufactured MDF panels using 15% gluing content of MgLS exhibited a deteriorated dimensional stability (thickness swelling and water absorption (24 h)).…”
Section: Physical Properties Of Particleboardscontrasting
confidence: 83%
“…The mean values of WA and TS after 2 and 24 h of immersion in water obtained in this study were also higher than the results reported by some researchers [62] in particleboards produced with lignin-phenol-formaldehyde resin with density of 750 and 950 kg/m 3 . In other works [38,40], it was also indicated that manufactured MDF panels using 15% gluing content of MgLS exhibited a deteriorated dimensional stability (thickness swelling and water absorption (24 h)).…”
Section: Physical Properties Of Particleboardscontrasting
confidence: 83%
“…Among the most requested, phenol-formaldehyde stands out, which is one of the main types of synthetic thermoset adhesive used by the wood panel industries. Widely used in the production of panels for structural purposes intended for the external environment, with or without protection (Iwakiri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Panels produced with wood particles, pressed with synthetic adhesives under heat and pressure, are called particleboards. For the production of particleboards in Brazil, the species of the genus Pinus and Eucalyptus from forest plantations are used (Iwakiri et al, 2019), but any material with chemical constitution similar to wood (cellulose, hemicellulose and lignin) can be used as raw material.…”
Section: Introductionmentioning
confidence: 99%
“…In the particleboard industry, in addition to the raw material, the adhesive is another factor of great importance. Resins based on urea-formaldehyde and phenol-formaldehyde are the main types of synthetic thermoset adhesives used by the wood particleboard industries (Iwakiri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation